МОНГОЛЧУУДЫН УЛС ТӨРИЙН ФИЛОСОФИ: УЛАМЖЛАЛТ ҮЗЭЛ САНАА - Д.Болд-Эрдэнэ (Politology, 2023)
The Mongols had traditional concept of political philosophy but some researchers hesitate that.The Mongols had a hundred year's custom of state and tactics to govern wisely. This tactics was their basis of political philosophy.